The Income Analysis of Blade Farming Businesses with Different Ownership Scales in Konda District South Konawe Regency - Malik Abdul Aziz; Abdi Abdi; Muhammad Aswar Limi (Department of Agribusiness, Halu Oleo University, 2022)
This research is motivated by the lack of management and management of cattle-breeding farms, which affects the income results of cattle breeding businesses on various ownership scales in the Konda District, South Konawe Regency. The purpose of the study was to find out the income of cattle breeding businesses on different ownership scales in the Konda District South Konawe Regency. The study's location was determined purposively by considering the village with the largest total cow population in the Konda District. The number of respondents to cattle breeding farmers is as many as 38 farmers. Data analysis uses descriptive quantitative data analysis by calculating costs, receipts, and revenues. The results showed that income for small-scale businesses ranged from IDR14.980.000 and for periodic medium businesses around IDR22.960.000 while for large-scale businesses around IDR28.185.000. The payment of cattle breeding business on various ownership scales in Konda District, South Konawe Regency, shows decent business income.